(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Tourism enterprise development plays a crucial role in the economic growth of regions and nations, contributing to employment generation, infrastructure development, and foreign exchange earnings. This study explores the economic theories underpinning tourism entrepreneurship, focusing on market structures, supply and demand dynamics, and investment models. Furthermore, it examines practical applications of these theories, including business strategies, financial planning, and government policies that foster entrepreneurial success in the tourism industry. By analyzing real-world case studies, the research identifies key drivers of sustainable tourism business growth, such as innovation, digital transformation, and stakeholder collaboration. The findings highlight the importance of integrating economic principles with strategic business practices to enhance competitiveness and resilience in tourism enterprises. This paper contributes to the academic discourse on tourism economics by providing insights into how theoretical foundations translate into practical applications for business sustainability and profitability.